Peningkatan Pengetahuan Tentang Kesiapan Mental Pada Ibu Hamil Menghadapi Persalinan Saat Pandemi Covid-19 di Posyandu - Evi Zulfiana; Adevia Maulida Cikmah; Ulfatul Latifah (Forum Kerjasama Pendidikan Tinggi, 2021)
Pregnancy is a life-changing journey by itself, even when the pandemic does not hit the world Anxiety in pregnant women can have an effect on the health of the mother and the fetus. Covid-19 pandemic as one of the influences of maternal anxiety in the face of childbirth. according to the American College of Obstetricians and Gynaecologists, so far, data show that pregnant women have a higher risk of developing the Covid-19 virus due to changes in the immune system that occur during pregnancy, can make pregnant women more susceptible to infection and more at risk of experiencing symptoms of severe and fatal diseases.The purpose of this devotion is to increase the knowledge of pregnant women about covid-19 and To increase the knowledge of pregnant women about mental preparation about facing childbirth during the covid-19 pandemic. The method of activities carried out is to provide health education that is useful to reduce the anxiety of pregnant women facing the preparation of childbirth during the covid-19 pandemic. The results of activities carried out by all pregnant women who participated in the class of pregnant women already know about the readiness to face childbirth during the pandemic.